Potential risk and promotive factors for serious delinquency in Japanese female youth. Issue 3 (2nd July 2016) - Bui, Laura; Farrington, David P.; Ueda, Mitsuaki
ABSTRACT: In Japan, concerns toward contemporary youth offending and violence have resulted in multiple changes in the treatment of youth. These changes are the result of negative societal perceptions of youth following a string of violent youth-on-youth murders and media sensationalizing juvenile crimes. Compared to what is known about male criminality, very little is known about female criminality, particularly about important risk and promotive factors for delinquency. Using the risk factor prevention paradigm, the study investigates potential risk and promotive factors for delinquency in 219 Osaka female youths, aged 15–18. The findings show that the strongest risk factors were high risk-taking and having troubled peers, whereas having a nonworking mother had promotive effects. Females were also compared to males, and the only significantly different factor was having a nonworking mother.